(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This study aims to describe the aesthetics of Ki Hajar Dewantara in the implementation of Javanese traditional music learning independent learning based on E-Gamelan at SMA Negeri 3 Pekalongan class XI.1 and describe the results of learning assessment in the form of practical tests and non-test-assessment-of-students-consisting-of-assessment: activeness, creativity, and cooperation. With the lack of gamelan equipment in schools, as well as the lack of human resources who teach gamelan, the E-Gamelan application is an effective solution that helps students recognize, appreciate, and understand gamelan music interactively. The use of EGamelan provides a variety of instruments, complexity, and harmony in learning gamelan music. This reflects Ki Hajar Dewantara’s aesthetic concept, which appreciates beauty in various forms. By utilizing 5.0 era technology in independent learning to learn traditional Central Javanese music, learners can more deeply understand gamelan music and develop learners’ musical skills. The research method used is mixed or combination (mixed method). Data collection techniques used observation, interviews, and documentation. The results showed (1) the beauty of a wide selection of instruments and variations in playing instruments. (2) the concept of complete aesthetics (volledigheid) appears in the variety of instruments provided. (3) the aesthetics of harmony (laras) reflects the concept of fusion and harmony between various instruments in gamelan music. The results of the research, cycle 1 of 34 learners, with 19 people (55.88%) getting sufficient scores (70-79) and 15 people (44.11%) getting fewer scores. In cycle 2 of 34 learners, 7 people (20.58%) got good grades (80-89) and 26 people (76.47%) got sufficient grades (70-79). The number of learners who scored above 70 or complete was 34 with an average of 78. Suggestions to improve the utilization of E-Gamelan in Javanese traditional music education, (1) development of content and application features. (2) teacher and instructor training. (3) integration with conventional learning.